Spelling errors among Hausa-speaking Arabic learners - Ibrahim, Rabiu Abubakar; bin Wan Solang, Wan Muhammad; bin Hassan, Abd Rauf (Human Resource Management Academic Research Society, 2024)
This study aimed to analyse spelling errors among students of Arabic as a second language. The analysis has been done by identifying its causes and the factors that lead to its occurrence and suggesting appropriate ways and strategies to overcome these errors. The researchers relied on the descriptive approach in this study. The analysis has been done using the test tool for the research sample and the interviews that have been conducted with Arabic language teachers and specialists in applied linguistics. After analysing the data collected by the researchers from the calendar tool, we found the reasons why students of the Arabic language at Sule Lamido University, Jigawa State make spelling errors. They are of two types: linguistic and non-linguistic reasons. The linguistic reasons are linguistic interference, incomplete application of the rules, false assumptions, overgeneralization, etc. As for the nonlinguistic reasons, they are: students’ strategies, lack of curriculum, and failure to use appropriate modern teaching methods. Following the interview, appropriate methods for overcoming these errors were proposed, including: hiring and training qualified teachers; using cooperative learning and the selective method instead of the standard method; reconsidering the curriculum; and intensifying the exercises where students made mistakes.